International trade and employment: Theory and evidence from Korean firms. (12th May 2021) - Jha, Priyaranjan; Lee, Jae Yoon; Liang, Yang; Mitra, Devashish
Abstract: We extend the small country trade model with firm heterogeneity (Demidova and Rodriguez‐Clare, Journal of International Economics, 90, 2013 and 266) to incorporate offshoring (along with final goods trade). We derive the firm‐level employment implications of output and input trade and trade costs and test them using Korean firm‐level data for the period 2006–2016. A key theoretical result is that the impact of a change in offshoring cost on employment depends crucially on the net substitutability between inputs where net substitutability is the difference between the elasticities of input substitution and output substitution. Empirically, we find that a decrease in the input trade cost reduces employment and the impact is stronger, the greater the net substitutability between inputs. Our 2SLS results with firm‐level imports (in place of trade costs) are consistent with our results with trade costs.